Fast Simple Determination of Oxygen in Reduced Graphene Oxide by Inert Gas Fusion Method. Issue 30 (14th August 2018) - Wang, Kuan; Chen, Na; Li, Bo; Zhou, Kai; Zheng, Wei; Liang, Qinghua
Abstract: A new method that combines inert gas fusion with infrared spectrometric detection for fast simple determination of total oxygen in reduced graphene oxide (RGO) has been established in this paper. The whole analyzing process was introduced, including calibration, temperature selection and sample weight selection. The equation of calculation the oxygen content of RGO in this method was given. The precision of the new method has been verified by measurement of a RGO sample. The RGO after measurement was characterized by X‐ray photoelectron spectroscopy (XPS). The relative standard deviation (RSD) of oxygen was 1.02%. The results were consistent with that obtained by the conventional classic method XPS. It has shown that the new method is accurate and efficient. The method of testing a RGO sample needs 140 s. The inert gas fusion‐infrared method is a fast simple method. Abstract : A new method that combines inert gas fusion with infrared spectrometric detection has been introduced for the fast simple determination of total oxygen (O) content in reduced graphene oxide (RGO) in the paper. The determining process of the method takes 140 s only. The method gives neither C/O atomic ratio nor mass ratio of local surface of RGO, but rapidly and directly determine the total O content of RGO sample. It is very meaningful for design of structure and property of RGO composite materials.